Evaluation of bone healing in trabeculae structure of mandibular corpus and angulus fracture patients with fractal dimension analysis - Poerwati Soetji Rahajoe; Hendra Sukawijaksa; Pingky Krisna Arindra; Silviana Farrah Diba (Journal of Oral Biology and Craniofacial Research)
Background: Fractures of the mandibular corpus and angulus are affected by different forces result from different strength of the muscles that influenced them. Therefore, it is presumed that there is a different in healing rate. Fractal dimension radiologic analysis assesses the trabecular pattern, due to it can be used to observe the healing process of bone fractures. Purpose: The study aimed to compare the healing process of mandibular corpus and angulus fractures with fractal dimension analysis (FD) of trabecular patterns on panoramic radiographs through ImageJ software as consideration to determine mastication loading time. Methods: This retrospective cross-sectional study observed medical records and panoramic radiographs of patients with a diagnosis of corpus and or mandibular angulus fractures undergoing open reduction (ORIF) 1 plate treatment combined with maxillomandibular fixation (MMF) at Hospital in 2017–2023. Observations were carried out on postoperative 1st day, 2nd week, 8–13th week and >13th week respectively. Results: Twenty-five subjects who met the inclusion requirements were involved in the study. The results of Two-Way ANOVA statistical test and Fisher's LSD post-hoc showed that the FD values of corpus fracture were significantly greater than that of mandibular angulus with p 0.000 (H1), 0.003 (H2), 0.03 (H3), 0.000 (H4) respectively. In both groups of mandibular corpus and angulus fractures, there was a significant effect of time with p = 0.00 in each group. The longer the observation time, the more trabeculae patterns were formed in the healing process of corpus and angulus fractures. Conclusion: Post ORIF observation of corpus fracture shows a greater trabecula formation value which indicates faster healing when compared to mandibular angulus fracture.